Copper and Melanin Play a Role in Myxococcus xanthus Predation on Sinorhizobium meliloti - Contreras-Moreno, Francisco Javier; Muñoz-Dorado, José; García-Tomsig, Natalia Isabel; Martínez-Navajas, Gonzalo; Pérez, Juana; Moraleda-Muñoz, Aurelio (Frontiers in Microbiology, 2020)
Myxococcus xanthus is a soil myxobacterium that exhibits a complex lifecycle with two multicellular stages: cooperative predation and development. During predation, myxobacterial cells produce a wide variety of secondary metabolites and hydrolytic enzymes to kill and consume the prey. It is known that eukaryotic predators, such as ameba and macrophages, introduce copper and other metals into the phagosomes to kill their prey by oxidative stress. However, the role of metals in bacterial predation has not yet been established. In this work, we have addressed the role of copper during predation of M. xanthus on Sinorhizobium meliloti. The use of biosensors, variable pressure scanning electron microscopy, high-resolution scanning transmission electron microscopy, and energy dispersive X ray analysis has revealed that copper accumulates in the region where predator and prey collide. This accumulation of metal up-regulates the expression of several mechanisms involved in copper detoxification in the predator (the P1B-ATPase CopA, the multicopper oxidase CuoA and the tripartite pump Cus2), and the production by the prey of copper-inducible melanin, which is a polymer with the ability to protect cells from oxidative stress. We have identified two genes in S. meliloti (encoding a tyrosinase and a multicopper oxidase) that participate in the biosynthesis of melanin. Analysis of prey survivability in the co-culture of M. xanthus and a mutant of S. meliloti in which the two genes involved in melanin biosynthesis have been deleted has revealed that this mutant is more sensitive to predation than the wild-type strain. These results indicate that copper plays a role in bacterial predation and that melanin is used by the prey to defend itself from the predator. Taking into consideration that S. meliloti is a nitrogen-fixing bacterium in symbiosis with legumes that coexists in soils with M. xanthus and that copper is a common metal found in this habitat as a consequence of several human activities, these results provide clear evidence that the accumulation of this metal in the soil may influence the microbial ecosystems by affecting bacterial predatory activities.